Letter from Marianne Homburger, Viktor Homburger, and Georg Bredig to Max Bredig, October 5, 1938 - Homburger, Marianne (1938)
Marianne Homburger (1903-1987) inquires about the well-being of her brother, Max Bredig (1902-1977), in the U.S.A and updates him on their family in Germany. Their father, Georg Bredig (1868-1944), recently turned seventy, their aunts are currently traveling, and Marianne's stepchildren are not attending school due to a polio outbreak. At the conclusion of the letter, Georg Bredig, and Marianne's husband, Viktor Homburger (1888-1968), include notes to Max.
Keywords: Homburger, Marianne, 1903-1986; Bredig, Max Albert, 1902-1977; Bredig, Georg, 1868-1944